2018
DOI: 10.1038/s41467-018-06568-5
|View full text |Cite
|
Sign up to set email alerts
|

REV-ERBα integrates colon clock with experimental colitis through regulation of NF-κB/NLRP3 axis

Abstract: The roles of Rev-erbα and circadian clock in colonic inflammation remain unclarified. Here we show colon clock genes (including Rev-erbα) are dysregulated in mice with DSS-induced colitis. In turn, disruption of the circadian clock exacerbates experimental colitis. Rev-erbα-deficient mice are more sensitive to DSS-induced colitis, supporting a critical role of Rev-erbα in disease development. Further, Rev-erbα ablation causes activation of Nlrp3 inflammasome in mice. Cell-based experiments reveal Rev-erbα inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
247
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 236 publications
(268 citation statements)
references
References 49 publications
(58 reference statements)
19
247
0
2
Order By: Relevance
“…mESCs are similar to cancer cells in terms of their high proliferative capacity. Consistent with a previous report studying cancer cell lines (11), we found that treatment with SR9009 for 2 d at a concentration (10 μM) used in many published studies (24,28,32,34,(42)(43)(44) reduced the viability of immortalized mouse and human cell lines, including some cancer cells (SI Appendix, Fig. S2A) but not fibroblasts (SI Appendix, Fig.…”
Section: Sr9009 Affects Cell Viability and Proliferation Independentsupporting
confidence: 91%
See 1 more Smart Citation
“…mESCs are similar to cancer cells in terms of their high proliferative capacity. Consistent with a previous report studying cancer cell lines (11), we found that treatment with SR9009 for 2 d at a concentration (10 μM) used in many published studies (24,28,32,34,(42)(43)(44) reduced the viability of immortalized mouse and human cell lines, including some cancer cells (SI Appendix, Fig. S2A) but not fibroblasts (SI Appendix, Fig.…”
Section: Sr9009 Affects Cell Viability and Proliferation Independentsupporting
confidence: 91%
“…That study treated cells for longer times (3-7 d), used SR9009 at a concentration of 20 μM, and mainly quantified cytotoxicity via a metabolic assay [NAD(P)H-based: WST-1]. In the present study we used 10 μM, which is the most commonly used concentration among published studies (24,28,32,34,(42)(43)(44), and quantified cytotoxicity via a metabolic assay as well as cell counting and EdU incorporation. Thus, our results demonstrate antiproliferative effects of SR9009 at shorter times of exposure and lower doses, which are seen even when REV-ERBs are drastically depleted from proliferating cells.…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK and NF-κB pathways are implicated in the control of synovial inflammation, hyperplasia, matrix degeneration, and bone destruction. There is a close correlation between NF-κB and NR1D1 16,32 . NR1D1 regulates experimental colitis by repressing the NF-κB/ NLRP3 axis 16 .…”
Section: Discussionmentioning
confidence: 84%
“…There is a close correlation between NF-κB and NR1D1 16,32 . NR1D1 regulates experimental colitis by repressing the NF-κB/ NLRP3 axis 16 . In addition, Stujanna and colleagues reported that SR9009 inhibited post-MI mortality and improved cardiac function by suppressing the MAPK and NF-κB pathways 33 .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation